A Systematic Analysis On The Admissibility Of Digital Documents As Evidence In Malaysian Syariah Courts - Wan Abdul Fattah Wan Ismail; Lukman Abdul Mutalib; Ahmad Syukran Baharuddin; Mohamad Aniq Aiman Alias (Universiti Putra Malaysia Press, 2024)
Indexed by WOS/Scopus/ERA/MyCite